Assessing Institutional Innovations to promote women-led informal seed systems in Eastern India - Puskur, Ranjitha (International Rice Research Institute, 2017)
Presented by Ranjitha Puskur (IRRI), as part of the Capacity Development Workshop hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 7-8 December 2017